(3cJGH GdePcQ hGdeDfKs - (3GdeanqVd Hf SdeI Hf YGUe, CHh WGdH,J (B290 (3g` s
(3ChdgG (B:s
(3GYde Cf GdaQb Hjf GdePcQ hGdeDfK KdGK YdGeGJ Jchf ai GdeDfK s
(3BNQgG (B:s
(3hGdCQfH CfKi hGdGSe GdePcQ hGdCfKi , aEPG GQGOhG GdPcQ bGdhG MRf , aGageg aEfg WQja s
(3HChd GdfSNI bQGAI dCHi GdaQL eMeO Hf EHQGgje GdGUHgGfi fGSN GdcJGH Ydi GdWjH GHf Ydi jQhHg Yf eMeO Hf ESeGYjd Hf HdHd Yf CHj WGdH GdeaVd Hf SdeI hJGQjN gPg GdbQGAI SfI (B352s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B314s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(100 / 8 (3b(B) s
Keywords: (3GddZIs